The Impact of Technology-Based Assessment on Enhancing Learning Quality in Junior High Schools in Cimahi City - Arfiani Yulianti Fiyul (The International Journal of Education Management and Sociology, 2025)
Technology-based assessment has emerged as a strategic innovation to enhance the quality of learning in junior high schools. This study aims to investigate the impact of technology-integrated assessments on students’ academic performance and learning motivation at SMP Negeri 4 Cimahi. Employing a quantitative approach with a quasi-experimental design, the study involved 80 eighth-grade students divided into an experimental group (technology-based assessment) and a control group (traditional assessment). Data were collected through standardized achievement tests and validated motivation questionnaires and analyzed using t-tests. The findings reveal that technology-based assessments significantly improve students' academic achievement and motivation, driven by instant feedback and interactive formats. Nonetheless, challenges such as infrastructure limitations and digital literacy gaps remain prevalent. The study concludes that technology-based assessment effectively supports more relevant and higher-quality learning in the digital age. It recommends teacher training and infrastructure investment to ensure sustainable implementation.